Al-inqisamiyyah wa azmah al-harakah al-shuyu'iyyah al-misriyyah hatta am 1965 (Markaz al-buhuth al-Arabiyyah wa al-Afriqiyyah, 2003)
'The schism and the crisis of the Egyptian communist movement until 1965' Politics.